No place like home: The chronotope of the haunted house in Peter Ackroyd's The House of Doctor Dee - Prosser, Ashleigh (2015)
This article seeks to explore the trope of haunting in contemporary English author Peter Ackroyd’s seventh novel The House of Doctor Dee, published in 1993. It will propose that Ackroyd’s novel is a Gothic narrative of uncanny returns, in which the spectres of the past are returned to the present through the temporal dislocation of space in the classical tradition of the ghost story, by the haunting of a house. The majority of the novel’s action is set in the house of its title, which is possessed by a mysterious history, ambiguous construction, and uncanny atmosphere. It provides the spatial medium through which the parallel narratives of the novel’s two narrators, the famous Elizabethan Doctor John Dee and the contemporary Londoner Matthew Palmer, can transhistorically haunt one another in an uncanny act that brings the dark history of the house and its inhabitants to light. This article will first consider whether the trope of the haunted house can be effectively read as a new kind of Bakhtinian literary chronotope inspired by that of the Gothic castle. It will then explore the significance of the chronotope of the haunted house in Ackroyd’s novel by employing the theory of the uncanny’s “return of the repressed”, and conclude by addressing how a chronotopic reading of the haunted house in The House of Doctor Dee reveals a ghost story that is both a modern Gothic narrative of the return of repressed trauma and a historical narrative of the visionary Gothic tradition.